1996
DOI: 10.1136/gut.38.5.707
|View full text |Cite
|
Sign up to set email alerts
|

Sulindac increases the expression of APC mRNA in malignant colonic epithelial cells: an in vitro study.

Abstract: Background-Sulindac is a non-steroidal anti-inflammatory drug which induces regression of colonic polyps in patients with familial adenomatous polyposis. Animal and in vitro studies have shown that both the sulphide metabolite of sulindac, which is able to inhibit cyclo-oxy-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…control cell to cell adhesion and cell rmigration (Nathke et al 1996: Barth et al 1997 (Schnitzler et al 1996). and it has been suggested that this effect might explain, at least in part.…”
Section: Discussionmentioning
confidence: 99%
“…control cell to cell adhesion and cell rmigration (Nathke et al 1996: Barth et al 1997 (Schnitzler et al 1996). and it has been suggested that this effect might explain, at least in part.…”
Section: Discussionmentioning
confidence: 99%
“…Sulindac sulfide induces a dose-dependent inhibition of cell proliferation on epithelial cell lines derived from colorectal cancer [35]. Sulindac sulfone reduces the growth of colon cancer precursors in rats [36].…”
Section: Discussionmentioning
confidence: 99%
“…One possible mechanism is that sulindac increases expression of APC (Schnitzler et al, 1996;Kishimoto et al, 2000) and that APC decreases survivin expression because, as we have shown (Zhang et al, 2001), APC downregulates survivin through the ␤-catenin:Tcf-4 pathway. However, HT-29 cells lack wild-type APC, which excludes this possibility.…”
Section: Discussionmentioning
confidence: 99%